Strategi Pelatihan dan Pengembangan Atlet Bola Basket di SMA 8 Bulukumba - Asdar, Andi Siti Nurhalizah; Armita, Andi; Azis, Akbar; Abrar, Abrar; Setiawan, A.Farhum; Wijayanto, Anggun Regitasari; B, Risman B (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2022)
This study aims to analyze the training and development strategies of basketball athletes at SMA Negeri 8 Bulukumba. Basketball is a sport that requires a combination of technical skills, physical condition, and optimal mentality. The research method used is descriptive qualitative with a case study approach. Data were collected through observation, in-depth interviews with coaches and athletes, and documentation of training programs. The research subjects consisted of 1 main coach, 2 assistant coaches, and 15 basketball athletes of SMA Negeri 8 Bulukumba. The results showed that the training strategy applied includes basic technical training, physical condition development, game tactics and strategy training, and athlete mental development. The training program is carried out 4 times a week with a duration of 2 hours per session. Evaluation of athletes' abilities is carried out periodically every month using skill and physical condition tests. Supporting factors include adequate facilities, school support, and high athlete motivation. Meanwhile, inhibiting factors include limited training time, unfavorable weather, and students' academic load. The recommendations given are the need to increase the intensity of training, add variations to training programs, and collaborate with professional basketball clubs to improve the quality of training.